Kualitas Pelayanan, Kepercayaan, dan Kepuasan Terhadap Loyalitas Nasabah - Kurniasih Kurniasih; Esti Dwi Rahmawati; Khabib Alia Akhmad (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2024)
Since its establishment, Islamic banks have experienced growth, especially in Indonesia with the largest Muslim population in the world who want an interest-free economic system (riba). This study aims to determine the relationship between Service Quality and Trust on Customer Loyalty through Satisfaction as an intervening variable. The sample was taken using a purposive sampling technique of 97 respondents, with data collected through a Likert scale questionnaire. This study is quantitative and analyzed using the Structural Equation Modeling (SEM PLS) 4.0 method. The results of the analysis show that Service Quality and Trust have a significant effect on Satisfaction, Trust has a significant effect on Customer Loyalty, while Service Quality does not have a significant effect on Customer Loyalty, Satisfaction has a significant effect on Customer Loyalty, Satisfaction is able to mediate the effect of Service Quality and Trust on Customer Loyalty.